2013
DOI: 10.3892/ijmm.2013.1436
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine inhibits angiotensin II-induced cardiomyocyte hypertrophy and tumor necrosis factor-α secretion through an NF-κB-dependent mechanism

Abstract: Tetramethylpyrazine (TMP), a bioactive compound isolated from the Chinese herb, Ligusticum wallichii Franchat, has been reported to play a protective role in cardiac diseases. However, the cellular and molecular mechanisms behind the protective effects of TMP on the heart remain to be elucidated. In this study, we aimed to determine the effects of TMP on angiotensin II (Ang II)-induced hypertrophy in neonatal rat cardiomyocytes and its possible mechanisms of action. In addition, we investigated whether TMP reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…These treatments have been shown to block the L-type calcium current in the ventricular myocytes and antagonize Ca 2+ influx in myocardial cells (23). Previous studies have also demonstrated that Danshen and Chuanxiong have an inhibitory effect on cardiac hypertrophy, as they have been shown to inhibit the formation of left ventricular hypertrophy in spontaneously hypertensive rats (1922). LIG is one of the active ingredients in Danshen and Chuanxiong.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These treatments have been shown to block the L-type calcium current in the ventricular myocytes and antagonize Ca 2+ influx in myocardial cells (23). Previous studies have also demonstrated that Danshen and Chuanxiong have an inhibitory effect on cardiac hypertrophy, as they have been shown to inhibit the formation of left ventricular hypertrophy in spontaneously hypertensive rats (1922). LIG is one of the active ingredients in Danshen and Chuanxiong.…”
Section: Discussionmentioning
confidence: 94%
“…These treatments significantly improve the patient’s clinical symptoms, signs and electrocardiograms. It has been reported that Danshen (19,20) and Chuanxiong (Szechwan Lovage Rhizome) (21,22) exhibit the characteristics of anti-ischemia, anti-hypoxia and calcium channel blockers. These treatments have been shown to block the L-type calcium current in the ventricular myocytes and antagonize Ca 2+ influx in myocardial cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…18 Briefly, 2 h after treatment with pioglitazone (0-20 µ mol/l) and apatinib (2 µ M), 0.1 µ M Ang II was used to stimulate cardiomyocyte hypertrophy and 1 µ Ci [ 3 H]-leucine was simultaneously added to each well. After stimulation with Ang II for 60 h, cells were harvested by precipitation with 10% trichloroacetic acid on ice for 30 min before being solubilized with 1 mol/l NaOH overnight at 4ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that TMP inhibits AngII-induced cardiomyocyte hypertrophy and TNF- α production via suppression of the NF- κ B pathway. This could provide new insight into the mechanisms underlying the protective effects of TMP in heart diseases [ 83 ].…”
Section: Tmp and Cardiovascular Diseasesmentioning
confidence: 99%